Phenotypic and functional changes of cytotoxic CD56pos natural T cells determine outcome of acute hepatitis C virus infection. - O'FARRELLY, CLIONA (My University, 2007)
Innate CD56(pos) natural killer (NK) and natural T (NT) cells comprise important hepatic antiviral effector lymphocytes whose activity is fine-tuned through surface NK receptors (NKRs). Dysregulation of NKRs in patients with long-standing hepatitis C virus (HCV) infection has been shown, but little is known regarding NKRs in acute infection. Treatment-naïve patients with acute HCV (n = 22), including 10 with spontaneous recovery, were prospectively studied. CD56(pos) NT levels were reduced early in acute HCV infection and did not fluctuate over time. In resolving HCV infection, NT cells with a more activated phenotype (lower CD158A and higher natural cytotoxicity receptor expression) at baseline predated spontaneous recovery. Moreover, NKG2A expression on CD56(+) NT cells correlated directly with circulating HCV RNA levels. Deficient interleukin-13 (IL-13) production by NT cells and reduced IL-2-activated killing (LAK) at baseline were associated with the ultimate development of persistence. These results indicate a previously unappreciated role for NT cells in acute HCV infection and identify a potential target for pharmacologic manipulation.
PUBLISHED
Keywords: Innate CD56(pos) natural killer (NK) and natural T (NT) cells; Innate CD56(pos) natural killer (NK) and natural T (NT) cells; Immunology, Inflammation & Infection